Determinants of diagnostic delay in chronic thromboembolic pulmonary hypertension: results from the European CTEPH Registry. Issue 6 (6th December 2018) - Klok, Frederikus A.; Barco, Stefano; Konstantinides, Stavros V.; Dartevelle, Philippe; Fadel, Elie; Jenkins, David; Kim, Nick H.; Madani, Michael; Matsubara, Hiromi; Mayer, Eckhard; Pepke-Zaba, Joanna; Delcroix, Marion; et al.
Chronic thromboembolic pulmonary hypertension (CTEPH) is characterised by chronic thrombi in the pulmonary arterial bed, causing pulmonary hypertension [1–3]. CTEPH is diagnosed in ∼3% of patients who survive a symptomatic acute pulmonary embolism (PE) [4]. While the surgical removal of chronic fibrotic thrombotic vascular occlusions by pulmonary endarterectomy (PEA) may cure most patients with CTEPH by normalising pulmonary artery haemodynamics and improving symptoms, patients who do not undergo the operation or do not undergo balloon pulmonary angioplasty have severe functional limitations, and poor quality of life and survival [5, 6]. Since the natural course of CTEPH involves progressive remodelling of the distal arteries and increase of pulmonary vascular resistance, which are both important determinants of outcome, early CTEPH diagnosis and referral to an expert centre are both critical for optimal treatment. It has, however, been shown that early diagnosis of CTEPH remains a major challenge, as demonstrated by a median diagnostic delay of 14 months identified in the large European CTEPH Registry [7]. The most likely explanations for this are diagnostic misclassifications as acute PE or other conditions, the nonspecific and often insidious clinical presentation of CTEPH, and the cumbersome diagnostic process of CTEPH, which involves multiple healthcare providers from different clinical specialties [8, 9]. The main determinants for and consequences of the diagnostic delay in CTEPH have not been studied. This study identified CTEPH patient characteristics that were predictive of longer diagnostic delay, which in turn was associated with higher pulmonary artery pressures and an increased risk of death http://ow.ly/yCZx30m9TQS